Polypoid Cystitis Unrelated To Indwelling Catheters: A Report Of Eight Patients - Kilic, Suleyman; Erguvan, Rezzan; Ipek, Deniz; Gunes, Ali; Gokce, Hasan; Engin Aydin, N.; Baydinc, Can (Annals of Medical Research, 2021)
None